2016
DOI: 10.1161/hypertensionaha.116.07357
|View full text |Cite
|
Sign up to set email alerts
|

Novel Therapeutic Role for Dipeptidyl Peptidase III in the Treatment of Hypertension

Abstract: Abstract-Dipeptidyl peptidase III (DPP III) cleaves dipeptide residues from the N terminus of polypeptides ranging from 3 to 10 amino acids in length and is implicated in pathophysiological processes through the breakdown of certain oligopeptides or their fragments. In this study, we newly identified the biochemical properties of DPP III for angiotensin II (Ang II), which consists of 8 amino acids. DPP III quickly and effectively digested Ang II with K m = 3.7×10 −6 mol/L. In the in vivo experiments, DPP III r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
69
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 52 publications
3
69
0
Order By: Relevance
“…Recently, Dipeptidyl peptidase III (DPP III, EC 3.4.14.4) has been reported to have anti-hypertensive, anti-cardiac hypertrophic and anti-fibrotic effects in mice [46]. DPP III is zine-dependent aminopeptidase and acts to preferentially cleave two amino acids (dipeptide residues) from the N-terminus of the oligopeptides in the serum, placenta, liver and brain [46,216218].…”
Section: New Insights Into the Roles And Therapeutic Implications mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Dipeptidyl peptidase III (DPP III, EC 3.4.14.4) has been reported to have anti-hypertensive, anti-cardiac hypertrophic and anti-fibrotic effects in mice [46]. DPP III is zine-dependent aminopeptidase and acts to preferentially cleave two amino acids (dipeptide residues) from the N-terminus of the oligopeptides in the serum, placenta, liver and brain [46,216218].…”
Section: New Insights Into the Roles And Therapeutic Implications mentioning
confidence: 99%
“…Recently, a number of new enzyme(s) and peptides have been reported to possess the vasodepressor properties, which may have novel therapeutic implications in cardiovascular, hypertensive, and renal diseases. Among these newly described enzyme(s) or peptides, dipeptidyl peptidase III, or DPP III [46], alamandine [4749], and angioprotectin [50,51], have been described as “new members” of the RAS or associated with the vasoprotective arms of the RAS. These enzyme(s) or peptides act to counter or opposing the actions of ANG II and may have a potential therapeutic role in treating hypertension associated with the activation of RAS [4648].…”
Section: Introductionmentioning
confidence: 99%
“…In this issue Pang et al, 1 in an elegant proof of concept study in mice, have shown that DPP III administered during 4 weeks (3× per week by intravenous injection), through catalytic reduction of Ang II levels, significantly diminished systolic blood pressure, cardiac hypertrophy, and myocardial fibrosis induced by Ang II in an extent at least similar to the effect of the angiotensin receptor blocker candesartan in effective antihypertensive doses. In the same experiments, they observed that DPP III diminished urine albumin excretion, kidney damage, and the renal protein levels of the pro inflammatory molecule monocyte chemoattractant protein-1 and the procoagulant platelet activator inhibitor-1.…”
mentioning
confidence: 99%
“…In this issue of Hypertension, the role of dipeptidyl peptidase III (DPP III) as a new antihypertensive candidate has been characterized in the mice. 1 Similar to DPP III, the carboxy peptidase ACE2 mediates degradation from Ang II to Ang (1-7) and also from Ang I to Ang (1)(2)(3)(4)(5)(6)(7)(8)(9). Both peptides contribute to the antihypertensive/ vasoprotective effects of the counterregulatory RAAS pathway ( Figure).…”
mentioning
confidence: 99%
See 1 more Smart Citation